(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Household food insecurity means that people either do not have access or unable to purchase food. In either case, they had to suffer from hunger and poverty. Food security is an important determinant to fulfill sustainable development goals. This study aims at determining the food security status and determinants of food insecurity in selected households from the coastal belt region of the Noakhali district, Bangladesh. Methods: A purposive sampling technique was employed for this cross-sectional study to select households. They were interviewed using a structured questionnaire in order to determine socioeconomic status and nutritional knowledge. Household Food Insecurity Access Scale was used to determine food insecurity. Results: Our study findings indicated that the majority of households (90.33%) were food secure. The study also revealed that the respondent’s level of education, level of nutritional knowledge, and level of monthly income are vital variables that have a significant correlation with food security in their households. However, the respondent’s age, gender did not have any significant correlation with food security. Having poor nutritional knowledge (OR=1.604, 95% CI=1.1,87.4) and lower-income level (OR= 7.636, 95% CI=1.14-51.18) have significantly increased the risk of food insecurity. Conclusion: Although food security status is satisfactory, policies should be set up to support nutrition education as well as micronutrient intake to achieve nutritional security.